USING PROFITABILITY RATIO AND ECONOMIC VALUE ADDED FOR FINANCIAL PERFORMANCE ANALYSIS IN AN INTEGRATED MEDIA COMPANY - Winarko, Hilarius Bambang; Jaya, Faris Indra (Journal of Business And Entrepreneurship, 2018)
The objective of this study is to analyze the financial performance of PT Media Nusantara Citra, Tbk. by utilizing profitability ratios and economic value added as the basic measurement. In this research, to calculate profitability ratios and economic value added, there are factors to employ, including COGS, NOPAT, invested capital, cost of debt, cost of equity, market value of the firm’s equity, income tax, market value of the firm’s liabilities, weighted average cost of capital (WACC), and capital charges. From a sample of the corporation’s annual reports over the 2007-2015 time span, our empirical results show a fluctual movement while showing an average growth of ROA at 11%, 15% ROE, 38% GPM, 28% NPM, and 47% TAT annually. A deeper analysis however reveals that the company is producing a high enough profit, hence the ability to cover its cost of capital over the following years. This paper also suggests several recommendations to maximize its value in the following years.